Penentuan Aktivitas dan Potensi Senyawa Kalkon Daun Jambu Air (Eugenia aquea Burm f) Terhadap Sel T47D Kanker Payudara Secara In Silico - Setyaningsih, Erwi Putri; Dari, Resti Wulan; Manalu, Rosario Trijuliamos (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2025)
Breast cancer is a malignant tumor caused by excessive expression of one or all three estrogen (ER) and progesterone (PR) proteins and Human Epidermal Growth Factor Receptor (HER2). Current breast cancer treatment generally uses chemotherapy, radiotherapy, hormone therapy, and surgery. The increasing need for new drugs with high selectivity, low toxicity, and good metabolic stability against breast cancer has led many researchers to explore Indonesia's natural resources to obtain drugs that have anticancer activity. Chalcone is a secondary metabolite of the flavonoid group with pharmacological activity as an anticancer. Four chalcone compounds in jambu air leaves (Eugenia aquea Burm f) have met the requirement Breast cancer is a malignant tumor caused by excessive expression of one or all three estrogen (ER) and progesterone (PR) proteins and Human Epidermal Growth Factor Receptor (HER2). Current breast cancer treatment generally uses chemotherapy, radiotherapy, hormone therapy, and surgery. The increasing need for new drugs with high selectivity, low toxicity, and good metabolic stability against breast cancer has led many researchers to explore Indonesia's natural resources to obtain drugs that have anticancer activity. Chalcone is a secondary metabolite of the flavonoid group with pharmacological activity as an anticancer. Four chalcone compounds in jambu air leaves (Eugenia aquea Burm f) have met the requirements for drug similarity testing. In silico research is the initial step in designing new drug discoveries because it is relatively faster and can handle thousands of compounds. This study aimed to determine the activity and potential of jambu air (Eugenia aquea Burm f) leaf chalcone compounds in inhibiting the target protein of breast cancer T47D cells in silico and its ADMET prediction. The research method is in silico, with molecular docking techniques using the YASARA View, Marvinsketch, PubChem, PLANTS, and Discovery Studio 2021 applications. The results of the molecular docking analysis of the target protein, namely, Myrigalon-b have the potential to inhibit HER2 protein, Myrigalon-g has the potential to inhibit ERÎ±, and phloretin has the potential to inhibit ERÎ². The ADMET prediction results of the Myrigalon-g and phloretin compounds have the best values.